Novel Cognitive Paradigms for the Detection of Memory Impairment in Preclinical Alzheimer's Disease. (April 2018) - Loewenstein, David A.; Curiel, Rosie E.; Duara, Ranjan; Buschke, Herman
In spite of advances in neuroimaging and other brain biomarkers to assess preclinical Alzheimer's disease (AD), cognitive assessment has relied on traditional memory paradigms developed well over six decades ago. This has led to a growing concern about their effectiveness in the early diagnosis of AD which is essential to develop preventive and early targeted interventions before the occurrence of multisystem brain degeneration. We describe the development of novel tests that are more cognitively challenging, minimize variability in learning strategies, enhance initial acquisition and retrieval using cues, and exploit vulnerabilities in persons with incipient AD such as the susceptibility to proactive semantic interference, and failure to recover from proactive semantic interference. The advantages of various novel memory assessment paradigms are examined as well as how they compare with traditional neuropsychological assessments of memory. Finally, future directions for the development of more effective assessment paradigms are suggested.